The Effect of Entrepreneurship Education and Entrepreneurial Perception on Student Satisfaction - Kevin Herdian Romdhoni; Marshella Auliana Geovani A.S (MIREJ: Multidisciplinary Innovation Research Journal, 2025)
This study aims to examine the effect of entrepreneurship education and entrepreneurial perception on individual satisfaction in the context of higher education. The background of this research highlights the growing importance of entrepreneurship as a key competency for future career development, as well as the need to understand how students' educational experiences and perceptions influence their overall satisfaction. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among the constructs. Data were collected through a questionnaire distributed to university students who had taken entrepreneurship-related courses. The findings reveal that while entrepreneurship education does not directly affect satisfaction, it significantly influences entrepreneurial perception, which mediates its impact on satisfaction. This result suggests that the effectiveness of entrepreneurship education is indirectly reflected through the development of positive perceptions, which enhance students' sense of fulfillment and engagement. The study contributes to the literature on entrepreneurship education by emphasizing the importance of perception as an intermediary variable, and offers practical implications for educators aiming to improve student satisfaction through curriculum design and instructional strategies.